Design and simulation of components of vacuum forming machine using household vacuum cleaner - Adhikari, Navaraj; Timilsina, Nirajan Sharma; Gautam, Sanskar; Kaphle, Snehraj; Shrestha, Pratisthit Lal (Journal of Engineering Issues and Solutions, 2021)
Plastic products ranging from toothbrushes to smartphones are an inseparable commodity in daily human life and their impact cannot be underestimated. This paper aims to design and simulate the vacuum forming process using readily available materials in context of Nepal. Vacuum forming process is a thermoforming process where the heated plastic sheet derives the shape of the mold through the application of vacuum and is used to make packaging products and other household products. Simulations were done to find out the optimum distance between the plastic sheet and the heater, arrangement of the wire in the heater, load bearing capacity of the design and the flow of vacuum in the arrangement. Nichrome wire coiled as heater coil is used as the heating material and laid in a spiral path with the plastic sheet 35mm below provided the best heating results and 1800W vacuum cleaner provided the necessary pressure of 85-90kPa and velocities of 100- 115m/s while the steel posts provided adequate strength.